2012
DOI: 10.1111/j.1365-2249.2012.04660.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels and mesenteric fat tissue expression of adiponectin and leptin in patients with Crohn's disease

Abstract: SummaryCrohn's disease (CD) is characterized by inflammation and an aetiology that is still unknown. Hypertrophy of mesenteric fat is a reflection of disease activity, as this fat covers the entire length of the affected area. Adipocytes synthesize leptin and adiponectin, adipocytokines responsible for pro-and anti-inflammatory effects. Therefore, we evaluated serum levels of adiponectin and leptin, as well as mesenteral expression of adiponectin in active CD and those in remission. Sixteen patients with ileoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 45 publications
(55 reference statements)
2
42
0
Order By: Relevance
“…The literature demonstrated that the increase in leptin was correlated with serum concentrations of IL-1b, cytokines, IL-6, and TNF-α, and that leptin may serve as a marker of active inflammation in IBD [20]. These elevated levels of leptin may be due to mesenteric fat hypertrophy, which is a reflection of disease activity, as this fat covers the entire affected area [21]. The relationship between increase in serum leptin level and presence of GD symptoms had been evaluated by Lankarani et al [9] in FD patients.…”
Section: Discussionmentioning
confidence: 99%
“…The literature demonstrated that the increase in leptin was correlated with serum concentrations of IL-1b, cytokines, IL-6, and TNF-α, and that leptin may serve as a marker of active inflammation in IBD [20]. These elevated levels of leptin may be due to mesenteric fat hypertrophy, which is a reflection of disease activity, as this fat covers the entire affected area [21]. The relationship between increase in serum leptin level and presence of GD symptoms had been evaluated by Lankarani et al [9] in FD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Talat Ayyildiz 1 *, Enver Dolar 2 , Nesrin Ugras 3 , Saduman Balaban Adim 3 , Omer Yerci 3 2011; Rodrigues et al, 2012). Adiponectin has been shown to demonstrate antitumor activity by suppressing tumor neoangiogenesis (Brakenhielm et al, 2004).…”
Section: Association Of Adiponectin Receptor (Adipo-r1/-r2) Expressiomentioning
confidence: 99%
“…Histological characteristics of the MAT in CD with reduced adipocyte size independent of the weight body have also been reported [17,18]. However, humoral and cellular changes in this adipose tissue are specific and differ from those observed in hypertrophied fat tissue of obese patients.…”
Section: Morphological Classification Of Adipose Tissue Depotsmentioning
confidence: 75%
“…However, Rodrigues and collaborators obtained low levels of serum and mesenteric adiponectin in MAT of CD, which suggests a defect in this anti-inflammatory pathway, which could in turn help to perpetuate a state of chronic inflammation [17]. Interestingly, all patients had the same BMI, below 25, and this alteration was independent of this parameter and of the presence of metabolic disorders.…”
Section: Molecular Characteristics Of the Mesenteric Adipose Tissue Imentioning
confidence: 97%
See 1 more Smart Citation